HETEROLOGIC EXPRESSION OF GENES THAT ROLE IN THE BIOSYNTHESIS OF POLY-(R)-3-HYDROXYBUTYRATE FROM BACILLUS THURINGIENSIS TH-01 IN HOST CELLS ESCHERICHIA COLI BL21(DE3) USING SYSTEM ONE PLASMID AND SYSTEM TWO PLASMID - Sabiqoh, Zuhdina
Poly-(R)-3-hydroxybutyrate (PHB) is a polyhydroxyalkanoate (PHA) derivative biodegradable plastic which can be synthesized by bacterial cells and has wide application potential. However, PHB production from natural organisms generally faces obstacles due to low productivity. On the other hand, recombinant DNA technology has proven to be an effective method for increasing biomolecules production in vivo. Previous research has succeeded in isolating the phaRBC cluster gene as essential genes for PHB biosynthesis in Bacillus thuringiensis TH- 01 which was isolated from thermite, consists of phaB (encoding acetoacetyl-CoA reductase protein), phaC and phaR genes (encoding PhaC and PhaR protein subunits of PHA synthase). This study aims to (1) obtain clone of phaA gene (encoding acetyl-CoA acetyl transferase protein) from B. thuringiensis TH-01 chromosomal DNA which is also essential for PHB biosynthesis, and (2) obtain two types of recombinant bacterial cells E. coli BL21 (DE3) containing recombinant plasmids to express the phaA and phaRBC genes of B. thuringiensis TH-01, using one plasmid system and the two plasmid system, respectively. This study successfully produced clone of phaA gene from B. thuringiensis TH-01 using cloning vector pGEM-T Easy and E. coli TOP10 as host cell. phaA gene was identified 1182 bp and having 100% identity with the acetyl-CoA acetyl transferase gene from Bacillus. The phaA gene clone, together with the phaRBC clone of B. thuringiensis TH-01, were successfully transferred from the cloning vector to pET- 30a (+) as expression vector resulting in pET-Bt-phaARBC which was used to transform E. coli BL21(DE3) host cell to create the PHB biosynthetic gene expression system with one plasmid. The two gene clones were also inserted in separate expression vectors, repectively pET-30a (+) and pET-16b, resulting recombinant plasmid pET-Bt-phaA and pET-Bt-phaRBC, for the two-plasmid expression system. Analysis of phaA gene expression using SDS PAGE showed the presence of PhaA protein bands with a size of ~ 41 kD, while phaRBC gene expression resulted in PhaR, PhaB, and PhaC protein bands with sizes of ~ 18.5 kD, ~ 26.5 kD, and ~ 41 , 7 kD. The efficiency of PHB production from recombinant cells E. coli BL21 (DE3) with one plasmid and two plasmid systems was not